A etnização do olhar através do turismo: etnografia de um parque temático étnico na Malásia (Sabah) - Bertrand Réau (Confins)
After presenting the historical and tourism context of Sabah in Malaysia, this paper analyses the staging of ethnicity for tourists within Sabah Village. Depending on the socio-cultural profile of the tourists, the visit can be perceived as: a reinforcement of nationalist sentiment, a reinforcement of a sense of superiority and difference between 'us' and 'them', or as a visit that fosters a quest for exoticism and primitivism. These different types of visits are linked by the playfulness of the activities offered.